Changes in vascular accesses and in incidence rates of dialysis-related bloodstream infections in Québec, Canada, 2011–2017. (8th April 2019) - Fortin, Élise; Ouakki, Manale; Tremblay, Claude; Villeneuve, Jasmin; Desmeules, Simon; Parisien, Natasha; Moisan, Danielle; Frenette, Charles
Abstract: Objective: Surveillance of dialysis-related bloodstream infections (DRBSIs) has been mandatory in Québec since April 2011. The aim of this study was to describe the epidemiology of DRBSIs in Québec. Methods: Cohort study of prevalent patients undergoing chronic dialysis in the 36 facilities that participated without interruption in the provincial surveillance, between April 2011 and March 2017. Two indicators were analyzed: proportion of patient months dialyzed using a fistula (a patient month is a 28-day cycle during which an individual patient received dialysis) and incidence rate of DRBSI. Binomial and Poisson regression with generalized estimating equations were used to describe the evolution of indicators over time and to quantify the association between facilities' proportion of fistulas and their incidence rate. Results: Globally, 42.6% of all patient months were dialyzed using a fistula, but there was a statistically significant decrease over time (46.2% in 2011–2012 to 39.3% in 2016–2017). Despite this decline in the use of fistulas, rates of DRBSIs have also decreased, going from 0.38 DRBSIs per 100 patient months in 2011–2012 to 0.23 DRBSIs per 100 patient months in 2016–2017. No association was found between facility use of fistulas and the rate of DRBSI. At the individual level, however, the DRBSI rate was 4.12 times higher for patients using a catheter. Conclusions: In Québec, the rate of DRBSIs has decreased over a 6-year period despite an increasing proportion of patients dialyzed by catheter.